Demand for and Classification of a Constitution Based on Its Content - Duc, Nguyen Quang (VNU Journal of Science: Legal Studies; Vol 34 No 4, 2018)
This article points out another approach based on the perception that constitutional differentiation may lead to the need of classification according to constitutional form and content. According to the author, it is a shortcoming in application if the constitutional classification by form is purely based on the two conventional constitution types: codified/inflexible and uncodified/flexible. Constitutional classification based on content provides a comprehensive and substantive review of each constitution by establishing a core value of constitutional paradigm, thought of modifications and the ability to adapt to social structure. This perception not only allows constitutional amendments to occur more often regardless of the constitution forms (codified/inflexible and uncodified/flexible constitution) but also supports application of constitutional models in the process of transformation. Keywords: Classification of constitution, classified by content, classified by form. References: [1] Markus Bockenforde - Nora Hedling - Winluck Wahiu, Những hướng dẫn thiết thực về xây dựng hiến pháp, Nguyễn Lệ Thu - Nguyễn Bích Thảo - Đỗ Giang Nam dịch, Nxb. Hồng Đức, Hà Nội, 2013. [2] Michele Brandt - Jill Cottrell, Yash Ghai - Anthony Regan, Xây dựng và sửa đổi hiến pháp: những lựa chọn cho quy trình, Cầm Thị Lai - Nguyễn Đăng Châu - Lê Thị Hồng Nhung dịch, Nxb. Hồng Đức, Hà Nội, 2013. [3] Nguyễn Văn Bông, Luật hiến pháp và chính trị học (bản in lần 2), Saigon, 1969. [4] Từ điển trực tuyến: http://tratu.soha.vn/dict/vn_vn/Ph%C3%A2n_ho%C3%A1 [5] Đào Trí Úc, “Hiến pháp trong đời sống xã hội và quốc gia”, Hiến pháp: những vấn đề lí luận và thực tiễn, Nxb. Đại học Quốc gia Hà Nội, Hà Nội, 2011. [6] Bùi Ngọc Sơn, “Các mô hình hiến pháp trên thế giới và một số kinh nghiệm rút ra cho Việt Nam”, Tạp chí Luật học (Trường Đại học Luật Hà Nội), số 10, Hà Nội, 2012. [7] Nguyễn Đức Lam, “So sánh Hiến pháp năm 1946 với một số hiến pháp đương thời”, Hiến pháp năm 1946: những giá trị lịch sử (Văn phòng Quốc hội), Nxb. Chính trị Quốc gia Sự thật, Hà Nội, 2017, tr. 275 - 281. [8] Hoàng Văn Tú, “Quan niệm về hiến pháp và xu hướng phát triển của hiến pháp”, Tạp chí Luật học (Trường Đại học Luật Hà Nội), số 10, Hà Nội, 2011. [9] Trần Ngọc Đường, Bàn về mô hình hiến pháp, Báo điện tử đại biểu nhân dân: http://www.daibieunhandan.vn/default.aspx?tabid=76&NewsId=228794 (ngày đăng: 07/11/2011; truy cập lần cuối: 13/11/2017). [10] Trần Thị Thu Thủy, Các mô hình Hiến pháp trong lịch sử lập hiến ở nước ta, Viện Nghiên cứu Lập pháp:http://vnclp.gov.vn/ct/cms/nghiencuuchuyende/Lists/nghiencuuphapluat/View_Detail.aspx?ItemID=192(Ngày đăng: 07/06/2013; truy cập lần cuối: 13/10/2017). [11] Samuel P. Hutington, The Third Wave: Democratization in the Late Twentieth Century, Norman: University of Oklahoma Press, 1991. [12] Khoa Luật - ĐHQG Hà Nội, Hiến pháp: những vấn đề lí luận và thực tiễn, Nxb. ĐHQG Hà Nội, Hà Nội, 2011.